Energy utilization in residential kitchens in Bauchi, Nigeria - Babayo Mohammed Adamu; Egho Yerima; Muhammed Murtala Bello (Economic and Environmental Studies (E&ES), 2017)
Energy has remained essential for cooking services by households through their kitchen. The source of this energy has remained multiple in nature, with a concise order of it being Modern or Traditional. This study through a survey, using four points scale and chi-square test of association of energy utilization by households in the University staff quarters explored the cooking energy so as to acknowledge the energy type used by households. The incentive for use and its impact on users and established that with a high level of education, only 9% of the households use LPG as a modern form of energy while the choice for Electricity and Kerosene has remained foremost in use by the household. The household size was noted to encourage the quantum of energy consumed as well as the persistent use of inferior energy like firewood which was penultimate looked as a rural energy. The study concludes that household in the study area use multiple energy sources to support their cooking activities due to affordability and it being dependable and easily obtainable even though not very durable and effective. It is noted that the study area has not obeyed the theory of utilizing the energy ladder concept.
Keywords: 330; Energy; Household; Kitchen; Choice; Utilization